2021
DOI: 10.1063/5.0060536
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the impacts of the refill valve diameter on prestrike occurrence in gas circuit breakers

Abstract: In puffer type Sulfur Hexafluoride (SF6) Circuit Breakers (CBs), the refill valve is the main inlet duct for the SF6 gas to enter the puffer volume. When the CB is closing and moving contacts and the nozzle are moving toward fixed contacts, the SF6 gas enters the puffer volume via the refill valve. Since changing the refill valve diameter can alter the direction of the SF6 gas motion in the closing operation of CBs, understanding its effects on CBs' function and performance may help to improve the CB design. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The model was developed to minimize the cancer cell density and the number of approved drugs and solved using a meta-search algorithm, and the experimental results show that the algorithm has superior performance in terms of convergence and scalability [16]. Homaee et al investigated the effect of the diameter of the refill valve on pre-strike during the closing process of a pressurized gas-type sulfur hexafluoride circuit breaker to establish a multi-physics field model, and numerical studies showed that the diameter of the refill valve has a great influence on the moment of pre-strike occurrence [17]. Luan et al established a low-carbon scheduling model to minimize the workshop completion time and energy cost considering sustainable development and proposed a biologically based heuristic algorithm [18].…”
Section: Introductionmentioning
confidence: 99%
“…The model was developed to minimize the cancer cell density and the number of approved drugs and solved using a meta-search algorithm, and the experimental results show that the algorithm has superior performance in terms of convergence and scalability [16]. Homaee et al investigated the effect of the diameter of the refill valve on pre-strike during the closing process of a pressurized gas-type sulfur hexafluoride circuit breaker to establish a multi-physics field model, and numerical studies showed that the diameter of the refill valve has a great influence on the moment of pre-strike occurrence [17]. Luan et al established a low-carbon scheduling model to minimize the workshop completion time and energy cost considering sustainable development and proposed a biologically based heuristic algorithm [18].…”
Section: Introductionmentioning
confidence: 99%